BICMAP-rhodium(I)-catalyzed asymmetric 1, 4-addition of arylboronic acids to coumarins. Issue 18 (15th October 2015) - Mino, Takashi; Miura, Kazuki; Taguchi, Hiroyuki; Watanabe, Kohei; Sakamoto, Masami
Graphical abstract: Abstract: Rhodium(I)-catalyzed asymmetric 1, 4-addition of arylboronic acids 2 to coumarins 1 using ( S )-BICMAP as a chiral ligand gave the desired 4-arylchroman-2-one derivatives 2 in good yields and with high enantioselectivities (up to 99% ee). Abstract : ( S )-4-Phenylchroman-2-one: C15 H12 O2 ee = 99% from HPLC [ α ]D 20 = +41.2 ( c 0.62, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( S ) Abstract : ( S )-4-(4-Methylphenyl)chroman-2-one: C16 H14 O2 ee = 98% from HPLC [ α ]D 20 = +45.5 ( c 0.45, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( S ) Abstract : ( S )-4-(4-Methoxyphenyl)chroman-2-one: C16 H14 O3 ee = 95% from HPLC [ α ]D 20 = +35.7 ( c 0.51, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( S ) Abstract : ( S )-4-(3-Methylphenyl)chroman-2-one: C16 H14 O2 ee = 95% from HPLC [ α ]D 20 = +41.5 ( c 0.50, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( S ) Abstract : ( S )-4-(3, 5-Dimethylphenyl)chroman-2-one: C17 H16 O2 ee = 99% from HPLC [ α ]D 20 = +40.1 ( c 0.40, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( S ) Abstract : ( S )-4-(2-Naphthalenyl)chroman-2-one: C19 H14 O2 ee = 80% from HPLC [ α ]D 20 = +42.6 ( c 0.45, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( S ) Abstract : ( S )-4-(2-Methylphenyl)chroman-2-one: C16 H14 O2 ee = 99% from HPLC [ α ]D 20 = +75.5 ( c 0.35, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( S ) Abstract : ( S )-6-Methyl-4-phenylchroman-2-one: C16 H14 O2 ee = 96% from HPLC [ α ]D 20 = +3.5 ( c 0.51, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( S ) Abstract : ( S )-7-Methyl-4-phenylchroman-2-one: C16 H14 O2 ee = 96% from HPLC [ α ]D 20 = +33.4 ( c 0.51, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( S ) Abstract : ( S )-7-Methoxy-4-phenylchroman-2-one: C16 H14 O2 ee = 98% from HPLC [ α ] 20 D = +41.0 ( c 0.37, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( S )